THE EFFECT OF CO-BRANDING ON BUYING INTEREST IN AEROSTREET PRODUCTS - Ahmad Maulana Lotian; Budi Rustandi Kartawinata (Jurnal Ekonomi, 2023)
Fashion is not only related to clothing, but there are other functional objects that can be combined with other elements so that they become tools that can show one's appearance in the general public. Fashion has a very wide market reach because almost some Indonesian people and even the world need the use of fashion to support daily activities. The method used in this research is quantitative method with descriptive research type. The population used in this study was people who knew Aerostreet with a sample of 100 respondents. The sampling used in this study is probability sampling. Based on the results of research using descriptive analysis with the help of SPSS, it shows that the Co-Branding variable which has t count 4.272 > 1.984 ttable with sig 0.000 < 0.05, then H0 is rejected and H1 is accepted, meaning that there is a positive influence from the Co-Branding variable (X) on the variable of buying interest (Y).